Performance Enhancement of Shell and Helical Coil Water Coolers Using Different Geometric and Fins Conditions. Issue 7 (30th April 2015) - Nada, S.A.; Eid, E.I.; Abd El Aziz, G.B.; Hassan, H.A.
Abstract : Experimental investigations of heat transfer characteristics and performance enhancement of shell and helical coil water coolers using external radial fins and different shells diameters were conducted. The study aims to enhance the water coolers performance in a trial to improve coil compactness. Two helical coils; one with a plain tube and the other with external radial fins, were tested in four shells of different tube diameters. Refrigerant passing inside the helical coils was used to cool water that enclose/passes in the space between the helical coil and the shell. Tests were conducted under mixed convection heat transfer regimes. Results showed performance and compactness enhancement with the insertion of external radial fins and increasing the shell diameter to helical coil diameter ratio. For nonfinned and finned coils, Nusselt number increased with increasing Reynolds number, Grashof number, and shell diameter. Correlations were predicted to give the Nusselt number in terms of Reynolds number, Grashof number, and shell diameters for finned and nonfinned helical coils. Correlations predictions were compared with present and previous experimental results and good agreements were obtained.